Heavy Metal–Resistant Plant Growth–Promoting Citrobacter werkmanii Strain WWN1 and Enterobacter cloacae Strain JWM6 Enhance Wheat (Triticum aestivum L.) Growth by Modulating Physiological Attributes and Some Key Antioxidants Under Multi-Metal Stress - Ajmal, Abdul Wahab; Yasmin, Humaira; Hassan, Muhammad Nadeem; Khan, Naeem; Jan, Basit Latief; Mumtaz, Saqib (Frontiers in Microbiology, 2022)
Heavy metals (HMs) contamination of agricultural soils due to wastewater irrigation is a major limiting factor for crop productivity. Plant growth promoting bacteria (PGPB) are used to lower the risk of HM toxicity and increase crop yield. We evaluated two HM resistant PGPB strains i.e., Citrobacter sp. and Enterobacter sp. isolated from wastewater irrigated agricultural soils for their efficacy to mitigate HM (Cd, Ni, and Pb) stress in a pot experiment. Increasing concentrations (0, 50, 100, 200 ppm) of each HM was used to challenge wheat plants. Heavy metal stress had a negative impact on wheat growth, biomass and physiology. The plants under HM stress accumulated more HMs in shoots and roots, resulting higher oxidative stress which is evident by elevated malondialdehyde (MDA) content in shoot and roots. Moreover, alteration in antioxidants like ascorbate peroxidase (APX), catalase (CAT), peroxidase (POD) and superoxide dismutase (SOD) were observed in plants under HM stress. The extent of damage was observed to be higher with elevating HM concentration. However, the inoculation of wheat plants with Citrobacter sp. and Enterobacter sp. (107cfu/ml) improved plants shoot length (11-42%), fresh weight (41-143%), dry weight (65-179%) and chlorophyll a content (4% -12%) under HM stress. Citrobacter sp. and Enterobacter sp. lowered the oxidative stress and enhanced the activities of antioxidants enzymes alone and in co-inoculation. However, seed inoculated with consortium showed overall better results in altering oxidative stress and decreasing heavy metal accumulation in wheat shoot and root tissues. The studied bacterial strains had effective biostimulation and bioremediation potential for wheat cultivated in multi HM contaminated soil. However, molecular mechanisms by which these strains alleviate HM stress in wheat plant are needed to be investigated.